2013
DOI: 10.1002/ijc.28267
|View full text |Cite
|
Sign up to set email alerts
|

αv‐Integrin isoform expression in primary human tumors and brain metastases

Abstract: To determine whether metastasis to brain is associated with altered expression patterns of integrins, we investigated the expression of avb3, avb5, avb6 and avb8 integrins in primary malignancies and metastases to brain of breast, lung and renal carcinomas and in malignant melanoma. Inhibitors of av integrins are currently in clinical trials for glioblastoma. The role of integrins in the process of brain metastasis from other human tumors is unknown. Immunohistochemistry with novel integrin subtype specific ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 47 publications
6
87
0
Order By: Relevance
“…S3). These observations are consistent with those reported in the literature (32,33). The selectivity of the b3 antibody was validated using tumor tissue sections derived from cell lines known to express or lack b3 as determined by flow cytometry.…”
Section: Expression Of Integrins Avb3 and Avb5 And Rgd-dpc Internalizsupporting
confidence: 94%
See 3 more Smart Citations
“…S3). These observations are consistent with those reported in the literature (32,33). The selectivity of the b3 antibody was validated using tumor tissue sections derived from cell lines known to express or lack b3 as determined by flow cytometry.…”
Section: Expression Of Integrins Avb3 and Avb5 And Rgd-dpc Internalizsupporting
confidence: 94%
“…In addition, the receptor/ligand pair or the target gene can be substituted when appropriate. The RGD mimetic used in the current study was designed to target integrins overexpressed in some ccRCC patients (32,33). We showed that the efficiency of RGD-DPC delivery to various tumor cells correlated with overall abundance of RGD-binding integrin expression, particularly avb3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is now overwhelming evidence for its role in the clinical progression of multiple human epithelial malignancies (colon, ovary, and brain), both from the in situ to the invasive stage as well as from the invasive stage to regional and distant metastasis 5, 6, 7. The addition of breast cancers to this long list of epithelial cancers where integrin α v β 6 plays a role in clinical progression is more recent.…”
Section: Introductionmentioning
confidence: 99%